Quality of the Service as a Competitive Advantage, Comparative Study of Parcel Companies - Soto Medina, Nereyda; Marañon Lizarraga , Sheila Suset; Palacios Valenzuela, Cesar Arturo; Aguilar Carvajal, Rosa Delia; Acosta Haro, Elizabeth (Unidad Editorial UPTC, 2023)
This research describes, compares and analyzes the competitive advantages generated by the quality of the service in parcel companies nowadays. Therefore, the main goal of this comparative study is to determine the factors by which the quality of the service creates a competitive advantage between these companies, taking as a sample two of the main parcel companies in Los Mochis, Sinaloa. It should be noted that these companies are currently booming, due to the rise of online shopping. In addition, customers seek speed, price and care of the merchandise in their deliveries. The study was carried out based on the methodology of case study, which uses experience for the transmission of knowledge such as the opinion of people about two companies in particular. This study was developed with the characteristics of a descriptive research, with a non-experimental design; as well, the quantitative approach was used since it was intended to describe and to know different opinions and perspectives from people towards the quality of the service. The information was collected by applying a survey in which the opinion of the people regarding the quality of the service provided by both companies was gathered through a system of direct well-ordered questions. According to the results obtained thanks to the application of the instrument, the hypothesis proposed in this study is accepted, which establishes that the competitive advantage generated by the quality of service of the Paquetexpress parcel company is superior to that of the Estafeta parcel company. JEL Codes: M0, M1 Received: 10/01/2023.  Accepted: 26/06/2023.  Published: 09/08/2023.